Louise builds a boat - Pfanner, Louise (New York : Orchard Books, 1990)
Louise imagines building her ideal boat, one with a wooden deck for games, a crow's nest for watching dolphins, and a figurehead to paint.
Booklist
School Library Journal
1.5
K-3
Keywords: Boats and boating -- Fiction; Boats and boating -- Fiction